Geothermal technology: Trends and potential role in a sustainable future. (15th August 2019) - Anderson, Austin; Rezaie, Behnaz
Highlights: Different geothermal technology and their advancement are summarized. The environmental impact of different geothermal technology is presented. The advantages and disadvantages of the technology are presented. The opportunities for improvement the geothermal technology are explored. The potential role of the geothermal technology in the sustainable future is discussed. Abstract: Rapid population growth as well as modern technology reliance lead to a greater demand for energy consumption. An ever growing focus on creating sustainable environment requires energy sources to be used with caution. Two effective solutions to address these concerns include utilizing renewable energy resources and increasing efficiencies of current technologies. Geothermal energy provides a renewable energy source that has potential to supply reasonable amounts of electricity, heating, and cooling. The present research elaborates upon methods of harnessing energy using various geothermal technologies. Various methods of performance improvement, as well as integration of geothermal technology with other renewable energy sources are also discussed. The environmental impact and economic viability of the technology are mapped as well. The advantages and disadvantages of the technology and opportunities for improvement are explored based on the recent studies. Briefly, the potential role of geothermal technology in a sustainable future is discussed in the study. Finally, the prospective topics of future research are presented for further investigation.